Literacy Habituation as a Social Practice in Journalistic Extracurricular Through the Publication of Al-Lababan Magazine at MAN 2 Pati - Imroatuth Thoyyibah; Didi Pramono (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2026)
The lack of literacy engagement in Indonesia is clearly manifested in the 2022 PISA data, which places the country near the bottom at 69th place out of 80 nations. To address this challenge, journalistic extracurricular activities have the potential to serve as a tool for structured and sustainable literacy habituation. This study aims to analyze the process of literacy habituation through journalistic extracurriculars at MAN 2 Pati using the perspective of Pierre Bourdieu’s Social Practice Theory. Data collection techniques were conducted through observation, interviews, questionnaires, and documentation involving the advisor (IF), the chairperson (ES), daily management (MY and DM), and 52 extracurricular members. The results indicate that literacy habituation is formed through three social practices within the journalistic arena: daily practices (routine news writing), weekly practices (mentoring and evaluation), and annual practices (Basic Journalistic Training and the publication of Al-Lababan magazine). These practices foster the habit of reading, writing, critical thinking, and communication skills. By connecting together various forms of capital (cultural, social, economic, and symbolic) the journalistic arena turns literacy into an internalized practice. This development is shaped by strong teamwork, mentorship, and institutional support, even as it contends with challenges like academic workload and time management. Journalistic extracurricular activities are proven effective in forming a literacy habitual that creates an intelligent, critical, and literate generation.